MHD waves in the plasma system with dipole magnetic field configuration - Cheremnykh, S.O.; Agapitov, O. (Advances in Astronomy and Space Physics, 2012)
The eigenmode spectrum of the ultra low frequency (ULF) waves in the Earth magnetosphere is discrete and consists of Alfvén and slow magnetosonic modes. Their interaction depends on ionospheric conductivity and the magnetic field curvature. We present the physical conditions of resonant ULF waves realization obtained for different wave polarization types. ULF waves with poloidal polarization are strongly coupled to slow magnetohydrodynamic (MHD) waves. The magnetic field pressure oscillates with 180° phase shift with respect to the plasma pressure. Thus, for such coupled waves the partial pressure compensation is observed. The crucial influence of the background magnetic field shear on the poloidal modes is shown. The toroidal field line resonant ULF waves do not have magnetic pressure and plasma pressure perturbations. Results presented in this paper are common for the ULF waves in the Earth's magnetosphere and include different scale disturbations. The verification of the obtained conditions with parameters of waves collected in the Earth's magnetosphere ULF is carried out by use of AMPTE/CCE and Equator-S data. The good agreement is obtained.